2017
DOI: 10.1016/j.clay.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

In-depth characterisation of a mixture composed of powder/pellets MX80 bentonite

Abstract: International audienceMixtures made up of bentonite powder and pellets are a possible candidate for making sealing plugs used in deep radioactive waste disposal due to their low permeability, high swelling capacity, favourable properties with respect to radionuclide retention and operational advantages in terms of placement in situ, which is much easier than that of pre-compacted bricks of bentonite/sand mixture. It is therefore essential to better understand their hydro-mechanical behaviour to optimize the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 16 publications
4
41
0
Order By: Relevance
“…The smallest pores are deemed intra-aggregate pores, while the larger pores are deemed inter-aggregate-pores. A qualitatively similar result was obtained by [3], who analysed a single pellet (ȡ d = 2.06 Mg/m 3 , suction 135 MPa) of MX-80 bentonite. Interestingly, the inter-aggregate porosity (with an average diameter around 4-5 ȝm) was found to represent barely 7% of the total porosity.…”
Section: Observed Behaviour Of Pellets and Pellet-based Materials 21supporting
confidence: 85%
See 2 more Smart Citations
“…The smallest pores are deemed intra-aggregate pores, while the larger pores are deemed inter-aggregate-pores. A qualitatively similar result was obtained by [3], who analysed a single pellet (ȡ d = 2.06 Mg/m 3 , suction 135 MPa) of MX-80 bentonite. Interestingly, the inter-aggregate porosity (with an average diameter around 4-5 ȝm) was found to represent barely 7% of the total porosity.…”
Section: Observed Behaviour Of Pellets and Pellet-based Materials 21supporting
confidence: 85%
“…Pellet samples present a multi-modal porous structure ( [1], [2]), which can be observed using techniques such as Mercury Intrusion Porosimetry (MIP) and X-ray computed microtomography. A single pellet exhibits a double porosity structure ( [1], [2], [3]), which is the result of the compaction on the dry side of optimum moisture content that is employed in the production process. Figure 1(b) from [1] presents the bimodal Pore Size Distribution (PSD) curve of a single, highly compacted pellet (ȡ d = 1.95 Mg/m 3 ) with characteristic pore sizes of 13 nm and 3 ȝm.…”
Section: Observed Behaviour Of Pellets and Pellet-based Materials 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Bentonite pellet mixtures have been proposed as one of the candidate filling materials of tunnels and boreholes in geological disposal of high-level radioactive waste (HLW), not only because of its low permeability, high swelling capacity and high radionuclide adsorption properties, but also its easier backfilling operation, less compaction effort needed and more economic-efficiency expected (Imber and Villar et al, 2006;Alonso et al, 2011;Molinero-Guerra et al, 2016). Once installed in the repository, bentonite pellets will be submitted to coupled hydro-mechanical loadings.…”
Section: Introductionmentioning
confidence: 99%
“…The swollen mixture will fill different voids and generate swelling pressure, ensuring the sealing of the storage system. Molinero Guerra et al (2017) used X-ray computed tomography (X-ray CT) to investigate the microstructure of pellet/powder bentonite and found that this mixture was characterized by an initial heterogeneous distribution of powder grains inside the inter-pellet pores. This initial state could greatly influence the saturation process and the corresponding structure changes.…”
Section: Introductionmentioning
confidence: 99%